1998
DOI: 10.1046/j.1471-4159.1998.71041511.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the GABA Shunt and the Importance of the GABA Shunt Versus the 2‐Oxoglutarate Dehydrogenase Pathway in GABAergic Neurons

Abstract: We investigated the activity of the cerebral GABA shunt relative to the overall cerebral tricarboxylic acid (TCA) cycle and the importance of the GABA shunt versus 2-oxoglutarate dehydrogenase for the conversion of 2-oxoglutarate into succinate in GABAergic neurons. Awake mice were dosed with [1-13C]glucose, and brain extracts were analyzed by 130 NMR spectroscopy. The percent enrichments of GABA C-2 and glutamate C-4 were the same: 5.0 ±1 .6 and 5.1 ±0.2%, respectively (mean ±SD). This, together with previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
36
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 23 publications
(43 reference statements)
6
36
0
1
Order By: Relevance
“…V GAD can be estimated if the shunt f lux in GABAergic neurons is known. In a 13 C NMR labeling study of mouse brain, Hassel et al (32) reported that in GABAergic neurons, glucose oxidation in the pathway from ␣-KG to succinate is divided about equally between the TCA cycle and the GABA shunt. In our study, V TCA(GABA) sums all pathways from ␣-KG to succinate, which includes the GABA shunt in GABAergic neurons (25).…”
Section: Discussionmentioning
confidence: 99%
“…V GAD can be estimated if the shunt f lux in GABAergic neurons is known. In a 13 C NMR labeling study of mouse brain, Hassel et al (32) reported that in GABAergic neurons, glucose oxidation in the pathway from ␣-KG to succinate is divided about equally between the TCA cycle and the GABA shunt. In our study, V TCA(GABA) sums all pathways from ␣-KG to succinate, which includes the GABA shunt in GABAergic neurons (25).…”
Section: Discussionmentioning
confidence: 99%
“…First, as glutamine synthesized in astrocytes serves as an important neuronal energy substrate and precursor of glutamate (Hertz et al, 1999), a limited supply of glutamine to neurons would additionally impair neuronal oxidative metabolism and deplete the neurotransmitter pool of glutamate as well. Second, the inability to convert glutamate to glutamine may represent one mechanism contributing to impaired reuptake of glutamate into astrocytes after manganese exposure (Hazell and Norenberg, 1997) C]glutamate rather than from astrocytic glutamine, may be the result of impaired reuptake via the GABA shunt, an important pathway for the reentry of GABA into the TCA cycle (Hassel et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…2 and 4a. Note that due to the marked reduction in the cerebral level and labeling of aspartate accompanied by acute GABA-T inhibition (14) (Fig. 4a), the weaker [3- 13 C]Asp signals at 2.66 and 2.79 ppm were not distinguishable from noise in the 40 L POCE spectra averaged over 11.5 min.…”
Section: In Vivo 1 H Spectroscopymentioning
confidence: 99%
“…The disruption of the recycling of endogenous carbon skeleton in GABAergic neurons caused by the acute inhibition of the GABA shunt is accompanied by a decrease in the total concentration of Glu and Gln. 13 C NMR studies have shown that astrocytic Gln acts as the primary precursor for GABA following acute GABA-T inhibition (3,13,14). Since astrocytes do not synthesize GABA (1), a direct in vivo measurement of the turnover of [2][3][4][5][6][7][8][9][10][11][12][13] C]GABA from [1-13 C]Glc following acute GABA-T inhibition should be useful for characterizing the metabolic flux between astrocytes and GABAergic neurons in the living brain.…”
mentioning
confidence: 99%
See 1 more Smart Citation